How has the war in Ukraine affected Russian sentiments? - Mikael Elinder; Oscar Erixson; Olle Hammar (Research Institute of Industrial Economics (IFN), 2024)
We analyze the effects of Russia's invasion of Ukraine, the partial military mobilization, and the Wagner Group rebellion on a broad set of sentiments in the Russian population, using the exogenous timing of surveys from Gallup World Poll and the Levada Center. Our results show strong rally 'round the flag effects and widespread domestic support for the war, sustained despite high casualties through strategic recruitment and economic compensations. While it thus seems unlikely that a public uprising will end the war soon, we also find that sentiments among Russians abroad have shifted against Putin, aligning with global views.
Keywords: D72; F51; H56; 330; War; Russia; Sentiments; Rally 'round the flag; Putin